Associations between psychotic symptoms and substance use in young offenders. (18th June 2015) - Degenhardt, Louisa; Coffey, Carolyn; Hearps, Stephen; Kinner, Stuart A.; Borschmann, Rohan; Moran, Paul; Patton, George
Abstract Introduction and Aims Substance use and psychotic symptoms/disorders are associated. There has been little examination of this issue in young offenders, despite elevated substance use in this group. Design and Methods Semistructured interviews were conducted by trained researchers with 514 young offenders. Psychotic symptoms were assessed using a previously validated screening measure, with scores ≥3 indicative of possible psychotic disorder. Associations between this indicator and patterns of offending, common symptoms of mental disorders and health risk behaviours, including substance use were examined. The extent to which substance use and psychotic symptoms remained associated after adjustment for possible confounding was evaluated. Results Thirteen percent screened positive for psychosis. Participants who screened positive for psychosis were more likely than those who did not to have: unstable housing; been expelled from school; a family history of substance use/mental health problems, and depressive symptoms. Amphetamine, sedative and cannabis dependence were all strongly associated with screening positive for psychosis. Screening positive remained significantly associated with amphetamine and sedative dependence, and daily cannabis and sedative use, in multivariable regressions. Discussion and Conclusions One in eight young offenders reported symptoms consistent with psychosis. Symptomatology was strongly associated with heavy use of a range of illicit drugs. Given the frequency of these symptoms and the potential for them to be related to or exacerbated by drug use, this study highlights the importance of co‐ordinated alcohol and other drugs and mental health treatment for young offenders, both due to co‐occurrence and given the possibility that treating SUDs may impact on mental health symptoms. [Degenhardt L, Coffey C, Hearps S, Kinner SA, Borschmann R, Moran P, Patton G. Associations between psychotic symptoms and substance use in young offenders. Drug Alcohol Rev 2015;34:673–682]